2020
DOI: 10.1136/bmjopen-2020-037198
|View full text |Cite
|
Sign up to set email alerts
|

Trial Of Neurostimulation In Conversion Symptoms (TONICS): a feasibility randomised controlled trial of transcranial magnetic stimulation for functional limb weakness

Abstract: ObjectivesTranscranial magnetic stimulation (TMS) has been used therapeutically for functional (conversion) motor symptoms but there is limited evidence for its efficacy and the optimal protocol. We examined the feasibility of a novel randomised controlled trial (RCT) protocol of TMS to treat functional limb weakness.DesignA double-blind (patient, outcome assessor) two parallel-arm, controlled RCT.SettingSpecialist neurology and neuropsychiatry services at a large National Health Service Foundation Trust in Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is worth noticing, however, that only one of these studies was controlled [29]; therefore, a placebo effect of rTMS cannot be excluded. This notion is further supported by other findings, such as patients' improvement with very low stimulation frequency, outside the range of plasticity-inducing rTMS protocols [30,35], in addition to strength increase with sham stimulation [31]. Along this line, it has been suggested that possible therapeutic effects of TMS on FP may rely on the demonstration of intact motor pathways to the patient in an objective way [33,34].…”
Section: Discussionmentioning
confidence: 60%
“…It is worth noticing, however, that only one of these studies was controlled [29]; therefore, a placebo effect of rTMS cannot be excluded. This notion is further supported by other findings, such as patients' improvement with very low stimulation frequency, outside the range of plasticity-inducing rTMS protocols [30,35], in addition to strength increase with sham stimulation [31]. Along this line, it has been suggested that possible therapeutic effects of TMS on FP may rely on the demonstration of intact motor pathways to the patient in an objective way [33,34].…”
Section: Discussionmentioning
confidence: 60%
“… 25 , 26 Some studies even report on the near-zero incidence of rTMS-relevant side effects. 27 , 28 On the other hand, as an additional approach, rTMS inevitably added to rehabilitative consumption and incidence of side effects. As a consequence, our radar chart further visually illustrated the total value of each rehabilitative strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also summarized the effect of Transcranial Magnetic Stimulation (TMS), which can improve the clinical picture, according to several observations (162)(163)(164), but they also commented that the mechanism is still unclear, addressing methodological bias (165). Interestingly, TMS was suggested to mainly act through a cognitivebehavioral mechanism (166), rather than by cortical excitability modulation.…”
Section: Psychotherapeutic Treatmentsmentioning
confidence: 99%